Akal dan Moralitas dalam Islam: Analisis Filosofis terhadap Konsep Tanggung Jawab Manusia - Rizka Nazli Phonna (Al-Widad, 2023)
This study aims to analyze the relationship between reason (‘aql) and morality in Islam and to explain how both serve as a philosophical foundation for the concept of human responsibility. The main focus of this study is to elaborate the role of reason as an ethical instrument in shaping moral awareness and its implications for human freedom and responsibility within the perspective of Islamic philosophy. This research employs a qualitative method using a library research approach. Data are obtained from classical Muslim philosophers such as Al-Farabi, Ibn Sina, Ibn Miskawayh, and Al-Ghazali, as well as relevant secondary literature. Data analysis is conducted using content analysis techniques through a philosophical approach to examine the conceptual relationship between reason, morality, and human responsibility. The findings show that reason in Islam functions not only as a cognitive tool but also as a moral instrument that directs human beings toward goodness. Morality provides the normative foundation for the use of reason, while human responsibility emerges from the integration of reason, freedom, and moral awareness.